Minimum Wage Analysis Using a Pre-Committed Research Design: Evidence through 2017 - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2019)
This paper presents results from the third year of a multi-year, pre-committed research design for analyzing recent minimum wage changes. Using ACS and CPS data through 2017, we find that relatively large minimum wage increases reduced employment among low-skilled individuals by just over 2 percentage points. The effects of smaller increases are more variable and estimates for inflation-indexed increases tend toward moderately positive values. The effects of smaller increases are relatively more positive when we analyze the CPS. The most recently enacted minimum wage changes tend to be positively correlated with employment among low-skilled individuals, while relatively early and large increases are strongly negatively correlated with employment. Analysis of future data will be needed to determine whether this apparent difference between short- and medium-run effects is systematic.
Keywords: J08; J23; J38; 330; minimum wages; employment; pre-commitment